Design and Build of Air Conditioners with Peltier Modules and PID Controls - Mahesa Sangga Bhuwana; Rasyida Shabihah Zukro Aini (Universitas PGRI Adi Buana Surabaya, 2024)
Air conditioners are among the technologies that have been increasingly common, as time has gone on, from personal comfort to room comfort. A multi-story building is one location that requires air conditioning. This is because the structure's air pressure will rise until a certain level, making the temperature too low, so air conditioning is necessary to maintain a comfortable temperature. Similarly, in tropical areas where the temperature exceeds what is reasonably comfortable. However, the current air conditioner technology has the potential to harm the environment. Since Freon, which is used in it, can pass through the ozone layer. Eventually, global warming will happen and the world will get hotter. The SHT21 sensor is the kind of sensor that will be utilized in this final project since it has strong and steady chemical resistance over time and uses the I2C interface. This type of sensor is also capable of being utilized as a calibrated ambient temperature sensor, with a digital output form already comprised. This sensor will enable us to create a PID system with feedback that monitors the temperature produced by the Peltier module along with reacting to controlled PID by delivering PWM into the driver, then subsequently transmits the signal to the Peltier module for monitoring. When the duty cycle is 100 percent or the PWM value is set to 255, the Peltier module generates a 12-volt voltage at its best. When duty cycle 0 percent or PWM value 0 is selected, the module stops functioning. It is anticipated that this system will advance toward a Freon-free air conditioning system.